1975
DOI: 10.1159/000458987
|View full text |Cite
|
Sign up to set email alerts
|

Glycolytic Enzymes in the Normal Human Term Placenta

Abstract: The enzymes hexokinase (HK), phosphoglucomutase (PGM), pyruvate kinase (PK) and lactate dehydrogenase (LDH) were assayed in villous tissue homogenates and cell fractions of normal human term placentas. Although lowest in activity and probably rate limiting in glycolysis, hexokinase is theoretically adequate to phosphorylate the total amount of glucose metabolized. PGM and PK activity were in the same range exceeding HK by 10-15 times, suggesting a largely increased breakdown of glycogenderived glucose in situa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
1

Year Published

1975
1975
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 17 publications
0
9
1
Order By: Relevance
“…No study is known to us in which the attempt is made to measure the blood content of the analyzed tissue samples and to correlate biochemical data to this con taminating component. In an earlier study on placental glycolytic enzymes we found a puz zling discrepancy between published data of placental protein content and our values (11). This could in part be explained by our proce dure of tissue processing which included inten sive perfusion of the intact organ with buffered saline to remove blood as complete as possible.…”
contrasting
confidence: 97%
See 3 more Smart Citations
“…No study is known to us in which the attempt is made to measure the blood content of the analyzed tissue samples and to correlate biochemical data to this con taminating component. In an earlier study on placental glycolytic enzymes we found a puz zling discrepancy between published data of placental protein content and our values (11). This could in part be explained by our proce dure of tissue processing which included inten sive perfusion of the intact organ with buffered saline to remove blood as complete as possible.…”
contrasting
confidence: 97%
“…On the light microscopical level the LDH was shown to be located mainly in the trophoblast and 'X' cells (1), whereas the intracellular distribution is not exactly known hitherto. In a former study on placental glycolytic enzymes the total LDH activity was recovered in the supernatant (11) but in vivo the isoenzymes may nevertheless be differentially associated to membrane structures (7), the soluble fractions being washed out more readily in damaged tissue samples. There is, however, no evidence for this suggestion.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In lens tissue of various mammalian species the particle-bound hexokinase was shown to be predominantly type I although a certain amount of type II may also be present [7], Information on type differences of human placental hexokinase is lacking hitherto. Starting from our previous observation that about 50% of the total placental hexokinase is bound to particles which are obviously mitochondria [21], we now investigated the possible existence of different isoenzymes in this organ. As was already shown by Walker et al [38] and confirmed by us, placenta does not contain glucokinase.…”
mentioning
confidence: 99%